Exchange bias in Pt doped NiMn thick films - (:unkn) unknown (AMER INST PHYSICS, 2010)
Magnetization and electron spin resonance (ESR) measurements were carried out on a 1.2 at. % Pt doped NiMn thin film (8000 angstrom) in the temperature range of 5-200 K for both parallel (field parallel to the film surface) and perpendicular configurations. M versus H loops were recorded at selected temperatures. Magnetization curves in the parallel configuration differ from those in the perpendicular geometry in many respects, including the anisotropy fields derived from these curves, and the coercivity. In addition, the temperature dependences of the magnetization in a small negative field (-0.5 Oe) and several larger positive fields will also be reported. All of these phenomena can be understood by the coexistence of Mn-rich and Mn-deficient aggregated granular regions coupled antiferromagnetically. Furthermore, the exchange stiffness constant (D), bulk anisotropy constant, and surface anisotropy constant were deduced from ESR measurements. The fitted ESR parameters are in good agreement with the behavior deduced from magnetization. (C) 2010 American Institute of Physics. [doi:10.1063/1.3364049]
Keywords: ANISOTROPY; FIELD